The role of the microbiota and metabolites in the treatment of pulmonary fibrosis with UC-MSCs: Integrating fecal metabolomics and 16S rDNA analysis - Yukai Luo; Shuang Zhou; Xiaojing Zhang; Yijian Lin; Jun Liu; Wenzhao Cheng; Yiming Zeng (PLoS ONE, 2025)
Introduction Pulmonary fibrosis (PF) is a chronic and irreversible interstitial lung disease characterized by a lack of effective therapies. Mesenchymal stem cells (MSCs) have garnered significant interest in the realm of lung regeneration due to their abundant availability, ease of isolation, and capacity for expansion. The objective of our study was to investigate the potential therapeutic role of umbilical cord-derived MSCs (UC-MSCs) in the management of PF, with a focus on the alterations in the gut microbiota and its metabolites during the use of UC-MSCs for the treatment of pulmonary fibrosis, as well as the possible mechanisms involved. Methods Bleomycin injection was utilized to establish a mouse model of lung fibrosis, followed by the application of 16S rDNA sequencing and LC–MS/MS metabolomics to explore the underlying mechanism of UC-MSC treatment for lung fibrosis. Seventy-five mice were allocated into five groups, namely Control, Model, and low/medium/high dose of UC-MSCs groups, and survival metrics, lung morphology, and the levels of the inflammatory cytokines TNF-α, IL-1β, IL-6, and TGF-β1 were subsequently evaluated. Fecal samples from six mice in each of the Control group, Model group, and UC-MSCs-M groups were collected randomly for 16S rDNA sequencing to analyze the gut microbiota and nontargeted metabolomics. Results In comparison to IPF model mice, the three treatment groups exhibited increased survival rates, restored alveolar morphology, and reduced levels of the inflammatory cytokines TNF-α, IL-1β, IL-6, and TGF-β1, confirming the anti-inflammatory properties of UC-MSCs in IPF treatment. The findings from the 16S rDNA assay indicate that UC-MSCs treatment effectively lower α-diversity induced such as Chao 1 and ACE, as well as β-diversity, leading to a decrease in microbiota abundance. The findings from the metabolomics analysis revealed that the metabolites exhibiting notable variances were primarily composed of Lipids and lipid-like molecules, Organoheterocyclic compounds, Organic acids and derivatives, and Benzenoids, indicating the potential of UC-MSCs to exert antifibrotic effects via these metabolic pathways. Conclusion Umbilical cord-derived mesenchymal stem cells (UC-MSCs) ameliorate bleomycin-induced pulmonary fibrosis symptoms in mice by exerting anti-inflammatory effects and mitigating pulmonary fibrosis through the modulation of gut microbiota disorders and their metabolism. These findings offer novel insights into the potential mechanisms and clinical utility of stem cell therapy for pulmonary fibrosis.